An audit of the time to initial treatment in avulsion injuries - KARGÜL, BETÜL (WILEY-BLACKWELL PUBLISHING, INC, 2009)
The prognosis of avulsed teeth depends on prompt and appropriate treatment. Good outcome requires education of the general public and non-dental professionals. Retrospective observational survey of case records of avulsion injuries attending a dental hospital trauma clinic. Data collected included: hospital number, date of birth, gender, source of patient's referral, date of trauma, number of avulsed teeth, place of initial presentation, storage, hours till initial presentation, and initial treatment. One hundred and twenty teeth with avulsion were identified in 75 children. The mean age of the patients was 9.8 years (SD = 2.3 years) at the time of trauma with avulsions recorded in 44 (58.7%) boys and in 31 (41.3%) girls. Only 51 (42.5%) teeth were stored in an appropriate medium before attendance at any site and only 48 (40%) of the teeth were seen within 1 h. 83.3% received emergency treatment at general hospital, 89.7% in dental practice and 92.9% at dental hospital. A minority of avulsion injuries were seen within the first hour and a minority were in appropriate storage medium at presentation. Geographical location plays a huge role in the time taken to reach secondary care. However, improving public and non-dental professional knowledge about tooth storage in avulsion injuries is critical to long-term prognosis of the teeth.
Keywords: TRAUMATIC DENTAL INJURIES; EMERGENCY MANAGEMENT; DENTOALVEOLAR TRAUMA; KNOWLEDGE; TEETH; TOOTH